Review on the Discovery of Water Absorbance Spectral Pattern in Aquaphotomics based on Chemometrics Analytical Tools - Ma, Xiaobo; Lin, Boran; Zhao, Bing; Wei, Xiaoying; Dong, Qin; Zhang, Hui; Li, Lian; Zang, Hengchang (Current Topics in Medicinal Chemistry, 2023)
Aquaphotomics, as a new discipline is a powerful tool for exploring the relationship between the structure of water and the function of matter by analyzing the interaction between water and light of various frequencies. However, chemometric tools, especially the Water Absorbance Spectral Pattern (WASP) determinations, are essential in this kind of data mining. In this review, different state-of-the-art chemometrics methods were introduced to determine the WASP of aqueous systems. We elucidate the methods used for identifying activated water bands in three aspects, namely: 1) improving spectral resolution; the complexity of water species in aqueous systems leads to a serious overlap of NIR spectral signals, therefore, we need to obtain reliable information hidden in spectra, 2) extracting spectral features; sometimes, certain spectral information cannot be revealed by simple data processing, it is necessary to extract deep data information, 3) overlapping peak separation; since the spectral signal is produced by multiple factors, overlapping peak separation can be used to facilitate the extraction of spectral components. The combined use of various methods can characterize the changes of different water species in the system with disturbance and can determine the WASP. WASPs of research systems vary from each other, and it is visually displayed in the form of the aquagram. As a new omics family member, aquaphotomics could be applied as a holistic marker in multidisciplinary fields.
Keywords: Aquaphotomics